Non-pharmacological treatments for asthma - Thomson, Neil (Henry Stewart Talks, 2014)
Non-pharmacological treatments in the management of patients with asthma, Avoidance measures, Dietary measures, Immunotherapy, Bronchial thermoplasty, Physical therapies, Psychological treatments, Complementary therapies, Need for high quality research to assess the effectiveness of some interventions